Case report: Mitral valve replacement for Libman-Sacks endocarditis and cerebral embolism of primary antiphospholipid syndrome - Liang, Huili; Ma, Chunyan; Chen, Xin (Frontiers in Cardiovascular Medicine, 2022)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by recurrent arteriovenous thrombosis and/or morbid pregnancy. Valve involvement is the most common cardiac manifestation of APS, with lesions characterized by valve thickening and vegetations known as Libman-Sacks endocarditis (LSE). This report discussed a rare case of a 26-year-old young woman diagnosed with primary APS with multiple cerebral infarctions and right middle cerebral artery occlusion that took place 3 years ago. On investigation, transthoracic echocardiography (TTE) revealed vegetations on both leaflets of the mitral valve, with mild to moderate mitral regurgitation. One year following hormone and anticoagulant treatment, mitral valve fibrosis and moderate to severe regurgitation were noted in the patient, after which mitral mechanical valve replacement was finally performed. Accordingly, this report suggests that the occurrence of LSE should be alerted during the examination of APS patients especially in those with cerebrovascular disease. Furthermore, establishing an early diagnosis and conducting close follow-ups are necessary for its timely intervention and treatment.